[tex]3\frac{3}{8} = \frac{8(3) + 3}{8} = \frac{27}{8}[/tex]
[tex]5\frac{1}{4} = \frac{4(5) + 1}{4} = \frac{21}{4}[/tex]
[tex]\frac{21 (miles)}{4}[/tex] ÷ [tex]\frac{27 (miles)}{8 (hour)}[/tex]
= [tex]\frac{21 (miles)}{4} * \frac{8 (hours)}{27 (miles)} = \frac{21(8)hours}{4(27)} = \frac{42}{27}hours[/tex]
[tex]\frac{42}{27} hours[/tex] = [tex]\frac{14}{9}= 1\frac{14-9}{9} hours = 1\frac{5}{9}hours[/tex]
Answer: [tex]1\frac{5}{9}hours[/tex]
How do I describe each pattern in words
13, 23, 33, 43
Gotcha!
As a whole, the pattern is +10. 13 to 23 you add 10. 23 to 33 you add 10. 33 to 43 you add 10. That's the best explanation.
HELP 1/7z+2=-6/7z what’s the solution set please send help I’m suffocating under homework
Isolate the z. Note the equal sign. Subtract 1/7z to both sides
1/7z (-1/7z) + 2 = -6/7z (-1/7z)
2 = -6/7z - 1/7z
Simplify. Combine like terms
2 = -7/7z
2 = -1z
Isolate the z. Divide -1 from both sides
(2)/-1 = (-1z)/-1
z = 2/-1
z = -2
-2 is your answer
hope this helps
Solve for x. x+2/3=−1/6 Enter your simplified answer in the box. x =
Im pretty sure your awnswer will be, x=−5/6
Subtract 2/3 from both sides.
x+2/3−2/3=−1/6−2/3
x=−5/6
Best of luck, terribly sorry if im wrong if i am my apologies
~Animaljamissofab ♥
Hannah reads at a constant rate of 3 pages every 8 minutes.
Write an equation that shows the relationship between p, the number of pages she reads, and m, the number of minutes she spends reading.
Answer:
[tex]m=\dfrac{8}{3}p[/tex]
Step-by-step explanation:
[tex]\begin{array}{ccc}3\ (pages)&-&8\ (min)\\p\ (pages)&-&m\ (min)\end{array}\qquad|\text{cross multiply}\\\\p\cdot8=3\cdot m\qquad|\text{divide both sides by 3}\\\\m=\dfrac{8p}{3}[/tex]
The equation is:
number of pages=reading speed×number of minutes
p = 3/8 × m
The correct answer is
p=3/8 m
6.58x - 8.36x = 3.98x - 27.33
Round your answer to the nearest hundredth
Answer:
-5.76x=-27.33
-6x=-27
Step-by-step explanation:
you would bring the 3.98 over to the other side, so it would be -3.98+6.58=2.6-8.39=-5.76
Which ordered pair is a solution of the equation?
y=-3x-4
Choose 1 answer:
(Choice A)
A
Only (-2,4)
(Choice B)
B
Only (-3,5)
(Choice C)
C
Both (-2,4) and (-3,5)
(Choice D)
D
Neither
Answer:
B.- Only (-3,5)
Step-by-step explanation:
In an ordered pair the first coordinate is the [tex]x[/tex] coordinate, and the second coordinate corresponds to the [tex]y[/tex] coordinate.
Then we must substitute the given value of [tex]x[/tex] in the equation and verify that we get in return the defined value for [tex]y[/tex].
the options are
[tex](-2,4)[/tex]in this one [tex]x = -2[/tex], and [tex]y=4[/tex], so let's confirm:
[tex]y=-3x-4\\y=-3(-2)-4\\y=-6-4\\y=2[/tex]this is not a solution since the [tex]y[/tex] values are not the same.
[tex](-3,5)[/tex]in this one [tex]x= -3[/tex] and [tex]y=5[/tex], let's also confirm:
[tex]y=-3(-3)-4\\y=9-4\\y=5[/tex]in this one the values for [tex]y[/tex] are equal, this is a solution for the equation.
What percent of the first 10 natural numbers are prime numbers? Answer in a percent please.
:)
So the first 10 are 1, 2, 3, 4, 5, 6, 7, 8, 9, 10. Since a prime number is only divisible by 1 and itself and greater than 1, our answers are 2, 3, 5, and 7. That's 4 numbers, or 4/10=0.4 of the 10. Since percentage is based out of 1, we can multiply 0.4 by 100 to get 40%. I hope that Helped :)
Whats the density of an object with the length of 5.0 cm a height of 3.0 and width of 15.0 cm and a mass of 24 grams
Answer:
The density of the object is [tex]0.1067[/tex] grams per cubic centimeter. (Rounded off to 4th decimal)
Step-by-step explanation:
Density = [Mass/Volume]
Here we have been given the dimensions of the object.
Volume = Height * Width * Length
Volume = [tex]3.0cm*15.0cm*5.0cm[/tex]
=[tex]225cm^{3}[/tex]
Now we can substitute the Mass and the Volume to the density equation.
Density = [Mass/Volume]
=[tex]\frac{24grams}{225cm^{3} }[/tex]
=[tex]0.1067[/tex] grams per cubic centimeter. (Rounded off to 4th decimal)
Simplify : (√x + √y ) (√x − √y) (x + y)(x2 + y2)
[tex]Solution, \mathrm{Expand}\::\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)\left(x+y\right)\left(x^2+y^2\right):\quad :x^4-:y^4[/tex]
[tex]Steps:[/tex]
[tex]\mathrm{Expand}\:\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right):\quad x-y, =\left(x-y\right)\left(x+y\right)\left(x^2+y^2\right)[/tex]
[tex]\mathrm{Expand}\:\left(x-y\right)\left(x+y\right):\quad x^2-y^2, =:\left(x^2-y^2\right)\left(x^2+y^2\right)[/tex]
[tex]\mathrm{Expand}\:\left(x^2-y^2\right)\left(x^2+y^2\right):\quad x^4-y^4, =:\left(x^4-y^4\right)[/tex]
[tex]\mathrm{Expand}\::\left(x^4-y^4\right):\quad :x^4-:y^4, =:x^4-:y^4[/tex]
The correct answer is [tex]x^4-y^4[/tex]
Hope this helps!!!
The simplification involves the use of the difference of squares identity on the first two terms, yielding (x - y). There's no further simplification possible for the remaining terms (x + y)(x^2 + y^2) under general conditions, resulting in the expression (x - y)(x + y)(x^2 + y^2).
The question involves the simplification of the given expression (
oot{x} + oot{y})(oot{x} - oot{y})(x + y)(x^2 + y^2). To simplify it, we will use the properties of square roots and algebraic identities.
Firstly, we use the difference of squares identity on the first two terms: (
oot{x} + oot{y})(oot{x} - oot{y}) = x - y.
Now, we look at the second pair of terms and realize that we can reshape the given expression using the properties of exponents: (x + y)(x^2 + y^2). Since both (x + y) and (x^2 + y^2) represent sums of powers of x and y, there is no direct simplification possible without additional constraints on x and y.
Therefore, the multiplication of these expressions gives us (x - y)(x + y)(x^2 + y^2) without further simplification under general conditions.
At Binh's Greenhouse in early spring, there are many greenhouse plants to repot and many outside plants to water. If it takes Binh 5 minutes to repot each plant and 2 minutes to water each plant, and he has at most 2 hours before the greenhouse opens, what inequality represents the time Binh has to repot and water the plants before the greenhouse opens? Let x represent the number of plants to repot, and y represent the number of plants to water.
2*y + 5*x < 2 hours But the units are not the same. The left side contains minutes and the right hours.
2y + 5x < 2*60
2y + 5x < 120 <<<<< Answer
Answer:
5x + 2x < 120
Step-by-step explanation:
Given:
Binh takes 5 minutes to repot each plant and 2 minutes to water each plant.
He has at most 2 hours.
Here "at most" represents by the inequality "<"
Let's convert 2 hours into minutes.
1 hour = 60 minutes
2 hours = 2×60 minutes = 120 minutes
Let x represent the number of plants to repot, and y represent the number of plants to water.
So, the given situation represented by
5x + 2x < 120
Select the correct answer from each drop-down menu.
A triangular piece of rubber is stretched equally from all sides, without distorting its shape, such that each side of the enlarged triangle is twice the length of the original side.
The area of the triangle to times the original area.
The area of the stretched triangle is four times the area of the original triangle
What is a Triangle?
A triangle is a plane figure or polygon with three sides and three angles.
A Triangle has three vertices and the sum of the interior angles add up to 180°
Let the Triangle be ΔABC , such that
∠A + ∠B + ∠C = 180°
The area of the triangle = ( 1/2 ) x Length x Base
For a right angle triangle
From the Pythagoras Theorem , The hypotenuse² = base² + height²
if a² + b² = c² , it is a right triangle
if a² + b² < c² , it is an obtuse triangle
if a² + b² > c² , it is an acute triangle
Given data ,
Let's assume that the original triangle has sides of length a, b, and c, and that its area is A. Without loss of generality, we can assume that side a is the shortest side.
After the rubber is stretched, each side of the enlarged triangle will be twice the length of its original length. Thus, the lengths of the sides of the stretched triangle will be 2a, 2b, and 2c.
Since the rubber is stretched equally from all sides, we know that each angle of the original triangle will be doubled. Therefore, the stretched triangle will be similar to the original triangle.
The area of a triangle is given by the formula:
A = (1/2) x base x height
where the base and height are the lengths of any two sides of the triangle that are perpendicular to each other.
Since the stretched triangle is similar to the original triangle, we can use the ratios of corresponding sides to find the lengths of the corresponding altitudes. Specifically, we have:
(altitude of stretched triangle corresponding to side 2a) = 2 x (altitude of original triangle corresponding to side a)
(altitude of stretched triangle corresponding to side 2b) = 2 x (altitude of original triangle corresponding to side b)
(altitude of stretched triangle corresponding to side 2c) = 2 x (altitude of original triangle corresponding to side c)
Therefore, the area of the stretched triangle is given by:
A' = (1/2) x (2a) x (2b) x (2/2) + (1/2) x (2b) x (2c) x (2/2) + (1/2) x (2c) x (2a) x (2/2)
Simplifying this expression gives:
A' = 4A
Hence , the area of the stretched triangle is four times the area of the original triangle.
To learn more about triangles click :
https://brainly.com/question/16739377
#SPJ7
Given the parent function f(x)=x2, what is the new equation if the function is translated 4 units to the right and 3 units down
Is the x2 supposed to be an exponent or no?
The new equation for the translated parent function f(x) = x^2, shifted 4 units right and 3 units down, is f(x) = (x - 4)^2 - 3.
Explanation:To translate the parent function f(x) = x^2 by 4 units to the right and 3 units down, we need to make the following adjustments:
The translation to the right will be represented by replacing x with (x - 4) in the equation.The translation down will be represented by subtracting 3 from the equation.So, the new equation is f(x) = (x - 4)^2 - 3.
Learn more about Translation of Parent Functions here:https://brainly.com/question/29253658
#SPJ11
In one week, a campground rented 18 cabins at $225 each. About how much did they collect in rent altogether?
Name the property of real numbers illustrated by the equation 5(x-3)=5x-15
This is known as the distributive property.
When you have a number outside of parentheses, (typically when there's a variable either inside or outside the parentheses), you can apply the number outside the parentheses to each term inside the parentheses, and the answer will still be equal.
Distributive Property is your answer.
In the case of "5(x - 3)", the parenthesis cannot be simplified, because you cannot combine a number and variable. To simplify, you must distribute the outside number (5), too all terms within the parenthesis
5(x - 3) = 5(x) + 5(-3)
Simplify.
5(x) = 5x
5(-3) = -15
5x - 15 is the answer (true, it makes the equation true)
Distribute Property is your answer
~Rise Above the Ordinary, Senpai
A contractor wants to replace the baseboard of a room whose length is 15 feet and width is 6 feet. How much will the baseboard cost if the material they will use is $5 per foot ?
It will cost $18.
15*6=90
90/5=18
It will cost $18.
The cost of the baseboard for $5 per foot whose length is 15 feet and width is 6 feet will be $ 210.
Given that:
Length of the baseboard = 15 feet
Width of the baseboard = 6 feet
The total space occupied by the baseboard can be calculated using the perimeter of the baseboard.
The perimeter of a rectangle can be calculated using the formula:
[tex]Perimeter = 2 \times(Length + Width)[/tex]
= [tex]2 \times(15 + 6)[/tex]
= [tex]2 \times 21[/tex]
= 42 feet
The cost of the baseboard can be calculated by multiplying the total length (42 feet) by the cost per foot ($5)
[tex]Cost \ of \ baseboard = Total\ length\times Cost \ per \ foot[/tex]
=[tex]42 \times 5[/tex]
= $210
Therefore, the cost of the baseboard for the room would be $210.
Learn more perimeter of a rectangle here:
https://brainly.com/question/15401834
#SPJ4
15 points! Thank you
[tex]10x^2+27x-28=10x^2+35x-8x-28=5x(2x+7)-4(2x+7)\\\\=(2x+7)(5x-4)\\\\Answer:\ D.\ 2x+7[/tex]
Which of the following expresses 16 + 36 by using the GCF of the two numbers?
4(4 + 9)
4(4 + 32)
8(2 + 28)
8(8 + 28)
16 + 36 = 52 so the answer would be A) 4(4 + 9) because that equals 52 as well.
PLEASE HELP THIS IS DUE TOMORROW
The change in temperature from 8am to 8pm is 4 degrees. The temperature at 8pm was -5 degrees. What is the temperature at 8am?
it's basically -5 plus 4
Which is -1
The temp. at 8am is -1 degrees.
1.588 x 10 to the negative 4th power
please help!
Cassidy wants to divide 4x^2−2x+3 by x + 2 using synthetic division.
Which answer shows the correct process?
(the answers are in the pictures below)
Refer to the image attached.
Since, we have to divide the polynomial [tex]4x^2-2x+3[/tex] by (x+2) using synthetic division.
We will divide the coefficients 4 -2 3 by -2
First term = 4 will remain same.
Second term = [tex](-2 \times 4) -2 = -8-2 = -10[/tex]
So, second term = -10
Third term = [tex](-2 \times -10)+3 = 23[/tex]
So, third term = 23
So, 4 -10 23 is the correct answer
So, Option 2 is the correct answer.
20 POINTS If each person paid an equal amount, who would save the most money?
My Numbers $47.94, $47.94, $48.60, $45
obviously $48.60 would save more.
Answer,
48.60
Hope this helps - Laura
:-)
solve for x b=1/6π n ^2 x
Answer:
[tex]\large\boxed{x=\dfrac{6b}{\pi n^2}}[/tex]
Step-by-step explanation:
[tex]b=\dfrac{1}{6}\pi n^2x\qquad\text{multiply both sides by 6}\\\\6b=\pi n^2x\qquad\text{divide both sides by}\ \pi n^2\neq0\\\\\dfrac{6b}{\pi n^2}=b[/tex]
Write the following products using exponents to express the results in a simpler form. (3 inches)(5 inches) and (5 feet)(2 feet)?
Answers:
___________________________________________________________
1) (3 inches)(5 inches) = (3 in)(5 in) = 3 * 5 * in * in = 15 * in * in = " 15 in² " .
___________________________________________________________
2) (5 feet)(2 feet) = (5 ft)(2ft) = 5 * 2 * ft * ft = 10 * ft * ft = " 10 ft² " .
___________________________________________________________
Final answer:
Exponents are used for repeated multiplication of the same number, hence, (3 inches)(5 inches) and (5 feet)(2 feet) cannot be simplified using exponents since they involve different numbers. Exponents and conversion factors are distinct mathematical tools, with the latter used for converting units of measure.
Explanation:
The question addresses using exponents to express products of the same units in a simpler form. The product of (3 inches)(5 inches) suggests multiplying these two measurements, however, when writing this product using exponents, we should consider that both are units of length, and thus their product will result in a unit of area, which is square inches (in2). We cannot simplify this expression further using exponents as they are not repeated multiplication of the same number.
On the other hand, for the product (5 feet)(2 feet), we again get an area, but this time in square feet (ft2). Still, there's no need for using exponents in this expression because we are not dealing with repeated multiplication of the same number.
It is important to note that exponents are used to represent repeated multiplication of the same number. For example, if we had (5 inches)(5 inches), we could write this as 5 inches squared (5 in)2, because it's 5 inches multiplied by itself. On the contrary, when multiplying different numbers, exponents don't apply.
When converting between different units of measure, as in converting feet to inches, we use conversion factors. For instance, 1 foot equals 12 inches, so by multiplying feet by 12, we can convert it to inches. Similarly, inches can be converted to feet by dividing by 12.
HELP AGIAN PLEASE
THANK YOU AGIAN!!
A is probably the most reasonable answer, of course it depends what situation you're in.
Logicly speaking, the phone would go to voicemail after about 30 seconds.
Echy~
What is the answer?
Markers are sold in boxes, packs, or as single markers.Each box has 10 packs. Each pack has 10 markers
There are 100 markers in each box, since one pack has 10 markers, and there are 10 packs inside the box, so you'd simply multiply 10 times 10 to get 100
Well each box has 100
but I don't understand what answer you are talking about. Sorry
What does it mean by property? Thank you!
This is talking about the different properties such as Commutative property and Associative Property, Distributive Law. This exact law is commutative law.
the length of a certain rectangle is 5cm more than 3 times its width. if the perimeter of the rectangle is 74 what is the length and width
The perimeter of a rectangle is the sum of all four sides of the rectangle.
(Perimeter = 2width + 2length)
Let's assume the width of the rectangle to be x.
For length, the statement says that is equals to 3 times the width (= 3x) and 5cm more meaning 5cm would be added to 3 times the width.
Width = x
Length = 3x + 5
Perimeter = 2x + 2(3x+5)
74 = 2x + (6x+10)
74 = 8x + 10
solve for x
8x = 74 - 10
x = 64/8, x=8
Width = 8
length = 3(8)+5 = 29
what is f(-3) if f(x) = 2x+1 + 5
Well we know that our function is -3, so we can plug this into the equation. \
f(x) = 2x + 1 + 5
f(-3) = 2(-3) + 1 + 5, now from here we simplify (:
-6 + 1 + 5 then finally we combine our like terms
-6 + 1 equals -5, then -5 + 5 equals 0
our final answer is zero if our function is f(-3) ((((((((((((((((((((((((((((((:
Vanessa buys a strip of 25 postage stamps. The strip of stamps is 21 7/8 inches long. How long is a strip after Vanessa uses 1 stamp?
Answer:
7/8
Step-by-step explanation:
The strip is 21 7/8 inches long. You need to make this into an improper fraction so you multiply 21x8= 168 and then add 7 to that which = 175. So the improper fraction is 175/8 (instead of 21 7/8). Now you just divide 175 by 25 which is 7. Each stamp is 7/8 inches long.
To find the new length of the strip after Vanessa uses one stamp, we first divide the initial length of the strip by the total number of stamps to find the length of one stamp. We then subtract this from the original length of the strip. The new length is 21 inches.
Explanation:This question is asking how long a strip of stamps is after Vanessa uses one of them. Given that the original strip is 21 7/8 inches long and includes 25 stamps, we can find the length of one stamp by dividing the total length of the strip by the total number of stamps. So, the length of one stamp is 21 7/8 ÷ 25.
We then subtract the length of this one stamp from the original length of the strip to find the new length:
Length of one stamp = 21 7/8 inches ÷ 25 = 0.875 inchesNew length of the strip = 21 7/8 inches - 0.875 inch = 21 inchesThe new length of the strip, after Vanessa uses one stamp, is therefore 21 inches.
Learn more about Length of Stamp Strip here:https://brainly.com/question/35061011
#SPJ3
What is the result of dividing x3−7 by x + 2?
The result of the division of x³-7 by x+2 will be (x²−2x+4)−15/(x+2).
What is the arithmetic operator?Arithmetic operators are four basic mathematical operations in which summation, subtraction, division, and multiplication involve.,
Division = divide any two numbers or variables called division.
For example 4/8
Multiplication = to multiply any two or more numbers or variables called multiplication.
Division of (x³-7) ÷ (x+2)
Keep quotient x² → (x³-7) - (x³+2x²) ⇒ remainder = -7-2x²
Next quotient -2x → (x³-7) - (-2x²-4x) ⇒ remainder = -7+4x
Next quotient 4 → (x³-7) - (8+4x) ⇒ reminder = -15
Therefore,
(x³-7) ÷ (x+2) = (x²−2x+4)−15/(x+2).
Hence "The result of the division of x³-7 by x+2 will be (x²−2x+4)−15/(x+2)".
To learn more about the arithmetic operators,
brainly.com/question/25834626
#SPJ2